Implementation of the Laravel Framework in Tutoring Information System (Case Study: Glow Math Course) - Anggraeni, Martina Meita; Susetyo, Yeremia Alfa (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The development of the Glow Math Course learning guidance information system using the Laravel framework has proven highly effective in accelerating the creation of secure and complex web applications. By utilizing the MVC architecture, Eloquent ORM, and Blade templating engine, as well as seamless integration with Midtrans, Laravel has streamlined the development process, improved efficiency, and delivered an intuitive user interface. Following User Acceptance Testing (UAT) with students, the evaluation showed that 85.92% of the system met the defined user requirements. Testing involved end users to ensure that the application met their expectations and needs. Additionally, system testing confirmed that the platform effectively supports the business processes of the tutoring service.